2017
DOI: 10.1089/cyber.2017.0271
|View full text |Cite
|
Sign up to set email alerts
|

Being There in the Midst of the Story: How Immersive Journalism Affects Our Perceptions and Cognitions

Abstract: Immersive journalism in the form of virtual reality (VR) headsets and 360°-video is becoming more mainstream and is much touted for inducing greater "presence" than traditional text. But, does this presence influence psychological outcomes of reading news, such as memory for story content, perceptions of credibility, and empathy felt toward story characters? We propose that two key technological affordances of VR (modality and interactivity) are responsible for triggering three presence-related cognitive heuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
1
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 28 publications
4
114
1
13
Order By: Relevance
“…This might be especially true if the photograph displays content that is interesting but not relevant for understanding the storyline, as it guides individuals' selective attention away from the main content and confuses their expectation what the story is actually about (Harp & Mayer, 1998; see also Lang, 1995). Recent experimental research corroborates this view, showing that 360-degree technology experienced on a laptop is rather distracting from than supporting a story (Van Damme, All, De Marez, & Van Leuven, 2018), demanding considerable cognitive costs (Sundar, Kang, & Oprean, 2017). The limited capacity model, however, also states that complex stimuli can increase memory for story content by causing an orienting response in news consumers that automatically shifts their attention to the stimulus and elicits additional cognitive resources to the encoding and storing of information (Lang, Bradley, Park, Shin, & Chung, 2006;Lang, Bolls, Potter, & Kawahara, 1999).…”
Section: Effects On Information Processing and Knowledge Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be especially true if the photograph displays content that is interesting but not relevant for understanding the storyline, as it guides individuals' selective attention away from the main content and confuses their expectation what the story is actually about (Harp & Mayer, 1998; see also Lang, 1995). Recent experimental research corroborates this view, showing that 360-degree technology experienced on a laptop is rather distracting from than supporting a story (Van Damme, All, De Marez, & Van Leuven, 2018), demanding considerable cognitive costs (Sundar, Kang, & Oprean, 2017). The limited capacity model, however, also states that complex stimuli can increase memory for story content by causing an orienting response in news consumers that automatically shifts their attention to the stimulus and elicits additional cognitive resources to the encoding and storing of information (Lang, Bradley, Park, Shin, & Chung, 2006;Lang, Bolls, Potter, & Kawahara, 1999).…”
Section: Effects On Information Processing and Knowledge Acquisitionmentioning
confidence: 99%
“…Incorporating more advanced and vivid forms of visualizations such as 360-degree photographs, however, might lead news consumers to divergent evaluations. As a spherical view of the camera's surroundings approximates physical reality more closely, they could trigger the basic rule of "seeing is believing" (Sundar et al, 2017). However, a compelling news experience might promote the positive impression of "novelty" or "coolness" just as well as the negative association of "all flash and no substance" (Sundar, 2008, p. 82).…”
Section: Effects On Perceived Message Credibilitymentioning
confidence: 99%
“…De hecho, la finalidad de los vídeos 360º y las experiencias de realidad virtual es permitir a los usuarios "experimentar incidentes y situaciones de primera mano, colocando al espectador en el centro de la experiencia y, por lo tanto, generando la sensación de estar en otro lugar y tiempo, viviendo las vidas y las historias de otras personas" (Soler-Adillon y Sora, 2018, p. 56). Es decir, tener la sensación de "estar ahí", en escena (De la Peña et al, 2010;Domínguez, 2013;Sundar, Kang & Oprean, 2017;Van den Broeck, Kawsar &Schöning, 2017).…”
Section: El Periodismo Inmersivo Como Renovación Narrativaunclassified
“…Immersion has been extensively studied in the virtual reality (VR) research community [35] and demonstrated as a positive engaging factor in immersive journalism [41]. The visualization community recently investigated the potential of immersive technology to provide new ways of representing, interacting and engaging with data [14].…”
Section: Immersive Visualizationmentioning
confidence: 99%
“…The second aspect we studied, immersion, is inspired by Immersive Journalism [41]. We hypothesized that people would enjoy being immersed within the data in a virtual reality (VR) environment.…”
Section: Introductionmentioning
confidence: 99%